Kolaborasi kampus–industri dalam program magang: Implikasi bagi pengembangan PT Dahana - Aura Puja Lestari; Muhammad Hilman Haidar; Gunaryo Gunaryo; Yusuf Bramastya Apriliyanto; Latisa Stefi Alivia; Adrian Rezki Anggara (Darmabakti: Jurnal Pengabdian kepada Masyarakat, 2025)
The internship program is a form of experiential learning designed to bridge the gap between theoretical knowledge acquired in higher education and practical experience in the workplace. This study aims to evaluate the performance of internship students participating in the Magang Generasi Bertalenta (MAGENTA) program at PT Dahana. The evaluation seeks to provide a comprehensive overview of students' competencies, discipline, responsibility, and adaptability throughout the internship period. This research employed a descriptive qualitative method with a survey approach. The primary data collection instrument was a structured questionnaire distributed to field supervisors who assessed the interns' performance. The collected data were analyzed to determine the effectiveness of the internship program in enhancing students' professional skills and its impact on the workplace environment. The results indicated that, in general, the internship students demonstrated good performance, characterized by a high level of discipline, a strong sense of responsibility, and quick adaptability to the company's work culture. The MAGENTA program at PT Dahana has proven to be effective in developing students' competencies and strengthening the partnership between higher education institutions and the industrial sector.